The role of politics and institutions in the Italian administrative reform trajectory - Ongaro, Edoardo (2011)
This article applies broad conceptual categories of campartive politics to the explanation of administrative reform in Italy. It takes as its arguement some lines of influence on public sector reforms of the features of the party system in Italy, the executive -legislative balance, the politician -bureaucrat relationship, and the role of administrative law. In the serch for explanation for the trajectory of administrative reform, pre-existing political and institutional factors also have to be interpreted through the lens of negotiated change occuring via processes of conversion and layering involving new and old institution that has taken place in Italy since the political crisis began in 1992. - Reproduced.
Keywords: Administrative reform - Italy; Administrative reform